Effect of nanoparticles shape on the cooling process of a lithium ion battery in geometry with capillary channels in the presence of phase change material. (April 2022) - Alsarraf, Jalal; Alnaqi, Abdulwahab A.; Al-Rashed, Abdullah A.A.A.
Highlights: The combination of PCM and nanofluid is used to cool a Li-ion battery. Effect of nanoparticle shape on the performance metrics are examined numerically. Brick-shaped nanoparticles have the highest reduction in battery temperature. Platelet-shaped nanoparticles have the lowest increment in the Nusselt number. Abstract: In this research, the impact of phase change material (PCM) and nanofluids (N-Fs) in a Li-ion battery cooling system (BCS) is evaluated numerically. A set of capillary channels are created inside the right and left of the Li-ion battery to flow N-Fs. PCMs are used between the channels. The N-Fs flow enters the BCS at a constant velocity and temperature and reduces the temperature of the battery and PCM. The numerical solution is performed using the finite element method. The results are compared with the previous results for Li-ion batteries and PCMs and the results exhibit excellent agreement. The results demonstrate that the use of nanoparticles (NPs) with different shapes can reduce the average temperature (T-Ave) of the battery and enhance the amount of Nusselt number (Nu). Also, they reduce the amount of molten PCM in the BCS at constant times. The application of NPs with high volume of fraction (VOFR) intensifies the fluid outlet temperature (T-Out). Brick-shaped NPs have the highest reduction in battery temperature (T-B) and the highest enhancement in the Nu, while platelet-shaped NPs have the lowest increment in the Nu and the lowest T-B. Over time, the T-B and the T-Out of the BCS are enhanced monotonically.